On (T,L)- Identification Function (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this paper, we study and introduce the notion of -identification function which is a function  from a topological  space  to another topological space  and   be two operators associative with    respectively, then  is called -identification function if and only if  is onto and  is -open set in  if and only if  is -open set in .